A Novel Single‐Atom Electrocatalyst Ti1/rGO for Efficient Cathodic Reduction in Hybrid Photovoltaics. Issue 19 (6th April 2020) - Liang, Suxia; Zhu, Chao; Zhang, Naitian; Zhang, Shuo; Qiao, Botao; Liu, Hua; Liu, Xiaoyan; Liu, Zheng; Song, Xuedan; Zhang, Heming; Hao, Ce; Shi, Yantao
Abstract: Single‐atom catalysts (SACs) are a frontier research topic in the catalysis community. Carbon materials decorated with atomically dispersed Ti are theoretically predicted with many attractive applications. However, such material has not been achieved so far. Herein, a Ti‐based SAC, consisting of isolated Ti anchored by oxygen atoms on reduced graphene oxide (rGO) (termed as Ti1 /rGO), is successfully synthesized. The structure of Ti1 /rGO is characterized by high‐angle annular dark‐field scanning transmission electron microscopy and X‐ray absorption fine structure spectroscopy, being determined to have a five coordinated local structure TiO5 . When serving as non‐Pt cathode material in dye‐sensitized solar cells (DSCs), Ti1 /rGO exhibits high electrocatalytic activity toward the tri‐iodide reduction reaction. The power conversion efficiency of DSCs based on Ti1 /rGO is comparable to that using conventional Pt cathode. The unique structure of TiO5 moieties and the crucial role of atomically dispersed Ti in Ti1 /rGO are well understood by experiments and density functional theory calculations. This emerging material shows potential applications in energy conversion and storage devices. Abstract : A titanium‐based single‐atom catalyst (SAC)—isolated Ti atoms anchored on reduced graphene oxide (Ti1 /rGO)—is successfully synthesized, characterized, and studied in detail. The experimental results indicate that oxygen atoms tightly anchor the isolated Ti atoms on the rGO with a five coordinated local structure TiO5 . This Ti‐based single‐atom catalyst is proved to be good cathode material with high electrocatalytic activity toward tri‐iodide reduction reaction in dye‐sensitized solar cells.